Adoption of recommended technologies by rubber growers in Kanyakumari district of Tamil Nadu - Somasundaram, J.I. Jergin; S. (Journal of Plantation Crops, 2018)
Rubber being an important plantation crop in our country, an attempt was made to analyse the adoption behaviour of rubber growers and the associated factors. The study was carried out in Thiruvattar block, Kanyakumari district of Tamil Nadu. Around 150 rubber growers were interviewed personally through a well structured and pre-tested interview schedule. Percentage analysis, cumulative frequency, simple correlation coefficient and multiple regressions were used for data analysis. Fourteen independent variables and one dependent variable were studied. Out of fourteen independent variables farming experience and scientific orientation had shown positive and significant association with adoption and mass media exposure had shown negative and significant relationship with the adoption. The results showed that 53.7 per cent of variation in the adoption and the results fit in the regression equation. Twenty five practices were identified to assess the adoption behaviour of rubber growers on rubber cultivation practices. Majority of the rubber growers had medium level of adoption on rubber cultivation practices. Regarding practice wise adoption, majority of the respondents adopted recommended spacing, weeding, first tapping during seventh year, tapping at the appropriate time, using tapping implements, yield stimulant and application of anti-coagulant in latex.